A post-occupancy study of ventilation effectiveness from high-resolution CO2 monitoring at live theatre events to mitigate airborne transmission of SARS-CoV-2. (September 2022) - Adzic, Filipa; Roberts, Ben M.; Hathway, Elizabeth Abigail; Kaur Matharu, Rupy; Ciric, Lena; Wild, Oliver; Cook, Malcolm; Malki-Epshtein, Liora
Abstract: Mass-gathering events were closed around the world in 2020 to minimise the spread of the SARS-CoV-2 virus. Emerging research on the transmission of SARS-CoV-2 emphasised the importance of sufficient ventilation. This paper presents the results of an indoor air quality (IAQ) monitoring study over 82 events in seven mechanically ventilated auditoria to support the UK government Events Research Programme. Indoor carbon dioxide concentration was measured at high resolution before, during, and after occupancy to allow for assessment of the ventilation systems. Generally, good indoor air quality was measured in all auditoria, with average IAQ found to be excellent or very good for 70% of spaces. In some auditoria, spatial variation in IAQ was identified, indicating poor mixing of the air. In addition, surface and air samples were taken and analysed for the presence of bacteria by culture and SARS-CoV-2 using RT-qPCR in one venue. SARS-CoV-2 RNA was detected on a small number of surfaces at very low copy numbers, which are unlikely to pose an infection risk. Under the ventilation strategies and occupancy levels investigated, it is likely that most theatres pose a low risk of long-range transmission of COVID-19. Highlights: Ventilation effectiveness was assessed in seven theatre auditoria. Parts of auditoria with poor mixing of air were identified using high-resolution CO2 monitoring. Demand-driven ventilation systems in monitored spaces do not always work as intended. Longer intervals can lead to a significant reduction of average CO2 in a space over the duration of an event. SARS-CoV-2 RNA was found at low concentrations in a minority of samples from one auditorium.